Transitivity : form, meaning, acquisition, and processing - Brandt, Patrick; García García, Marco (Linguistik aktuell, 2010)
What happens when a canonically transitive form meets a canonically transitive meaning, and what happens when this doesn't happen? How do dyadic forms relate to monadic ones, and what are the entailments of the operations that the grammar uses to relate one to the other? Collecting original expert work from acquisition, processing, typological and theoretical syntax-semantics research, this volume provides a state of the art as well as cutting edge discussion of central issues in the realm of Transitivity. These include the definition and role of "Natural Transitivity", the interpretation and